2022
DOI: 10.1136/bcr-2021-245021
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring of the resting heart rate using a fitness tracker smartwatch application leads to an early diagnosis of large vessel vasculitis

Abstract: Giant cell arteritis can involve both cranial and extracranial arteries. Isolated extracranial large vessel vasculitis more often manifests with non-specific constitutional symptoms, causing a diagnostic delay. We report the case of a 57-year-old Caucasian female patient presenting with persistently elevated resting heart rate, as revealed by a smartwatch healthcare application, and non-specific constitutional symptoms. Imaging revealed inflammation of the aorta, bilateral subclavian and axillary arteries, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A clinical trial with over 60 adults showed that wearing smartwatches with blood-pressure-monitoring features lowered the patients’ blood pressure and resting heart rate, elucidating the effect of self-monitoring [ 48 ]. Self-monitoring can also lead to early diagnosis [ 49 ]. In a study by Rens et al, cardiovascular disease patients were made to take a 6-minute walk test (6MWT) and their activity data were collected with an iPhone and an Apple Watch using the VascTrac app.…”
Section: Wearables As Digital Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical trial with over 60 adults showed that wearing smartwatches with blood-pressure-monitoring features lowered the patients’ blood pressure and resting heart rate, elucidating the effect of self-monitoring [ 48 ]. Self-monitoring can also lead to early diagnosis [ 49 ]. In a study by Rens et al, cardiovascular disease patients were made to take a 6-minute walk test (6MWT) and their activity data were collected with an iPhone and an Apple Watch using the VascTrac app.…”
Section: Wearables As Digital Diagnosticsmentioning
confidence: 99%
“…It was able to detect COVID-19 in the pre-symptomatic period as well as the symptomatic phase of the patients, with a precision score of 0.91 (CI: 0.854–0.967) [ 10 ]. Cho et al proposed a one-class SVM method that can detect COVID-19 23.5–40% earlier compared to the method of Mishra et al [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ,…”
Section: Wearables As Digital Diagnosticsmentioning
confidence: 99%